A new species of Spirophilometra (Nematoda: Philometridae) from the yellowfin snook Centropomus robalito (Osteichthyes) in southern Mexico - Moravec, Frantisek; Santana-Piñeros, Ana María; González-Solís, David; Torres-Huerta, Ana María (Folia parasitologica, 2007)
A new nematode species, Spirophilometra pacifica sp. n. (Philometridae), is described from gravid female specimens collected from the mouth cavity (the upper palate) of the fish (yellow snook) Centropomus robalito (Centropomidae, Perciformes) from the Chantuto-Panzacola system, Chiapas, in the Pacific coast of Mexico. Its morphology is very similar to that of the species originally described as Philometra centropomi Caballero, 1974, but the gravid females of S. pacifica are about three times longer (body length 11.63-18.17 mm); host species and the geographical distribution of both these forms also differ. Scanning electron microscope (SEM) examination of S. pacifica, used for the first time for a Spirophilometra species, confirmed the presence of numerous minute cuticular spines on the body surface, 14 cephalic papillae arranged in two circlets, and two small lateral papilla-like caudal projections. It is evident that some features of P. centropomi were incorrectly described (its types are not available) and this species is now transferred to Spirophilometra as S. centropomi (Caballero, 1974) comb. n.
Keywords: Nematoda; hlístice; nemoci ryb; Animals; Mexiko; Nematode Infections; zvířata; Perciformes; Fish Diseases; Mexico; nematodózy